The evils of forced migration: Do integration policies alleviate migrants' economic situations? - Oliver Falck; Stephan Heblich; Susanne Link (Institute for the Study of Labor (IZA), 2011)
Armed conflicts, natural disasters and infrastructure projects continue to force millions into migration. This is especially true for developing countries. After World War II, about 8 million ethnic Germans experienced a similar situation when forced to leave their homelands and settle within the new borders of West Germany. Subsequently, a law was introduced to foster their labor market integration. We evaluate the success of this law using unique retrospective individual-level panel data. We find that the law improved expellees' overall situation but failed to restore their pre-war occupation status. This holds implications for the design of integration policies today.
urn:nbn:de:101:1-201107133425
Keywords: N30; J61; D04; 330; forced migration; integration policy; difference-in-differences; Germany